A surprising palmar nevus: A case report - Rana Rafiei; Seyyedezeinab Azimi; Alireza Sheibani; Behnam Rafiee; Sara Najirad (Our Dermatology Online, 2018)
Raised palmar or plantar nevus especially in white people is an unusual feature. We present an uncommon palmar compound nevus in a 26-year-old woman with a large diameter (6 mm) which had a collaret-shaped margin. In histopathologic evaluation intralymphatic protrusions of nevic nests were noted. This case was surprising to us for these reasons: size, shape, location and histopathology of the lesion. Palmar nevi are usually junctional (flat) and below 3 mm diameter and intra lymphatic protrusion or invasion in nevi is an extremely rare phenomenon.